Carbon isotope fractionation for cotton genotype selection - Brito, Giovani Greigh De; Suassuna, Nelson Dias; Diola, Valdir; Sofiatti, Valdinei; Ducatti, Carlos; Silva, Evandro Tadeu Da; Morello, Camilo De Lelis (Embrapa Informação TecnológicaPesquisa Agropecuária Brasileira, 2014)
The objective of this work was to evaluate the carbon isotope fractionation as a phenomic facility for cotton selection in contrasting environments and to assess its relationship with yield components. The experiments were carried out in a randomized block design, with four replicates, in the municipalities of Santa Helena de Goiás (SHGO) and Montividiu (MONT), in the state of Goiás, Brazil. The analysis of carbon isotope discrimination (Δ) was performed in 15 breeding lines and three cultivars. Subsequently, the root growth kinetic and root system architecture from the selected genotypes were determined. In both locations, Δ analyses were suitable to discriminate cotton genotypes. There was a positive correlation between Δ and seed-cotton yield in SHGO, where water deficit was more severe. In this site, the negative correlations found between Δ and fiber percentage indicate an integrative effect of gas exchange on Δ and its association with yield components. As for root robustness and growth kinetic, the GO 05 809 genotype performance contributes to sustain the highest values of Δ found in MONT, where edaphoclimatic conditions were more suitable for cotton. The use of Δ analysis as a phenomic facility can help to select cotton genotypes, in order to obtain plants with higher efficiency for gas exchange and water use.

O objetivo deste trabalho foi avaliar o fracionamento isotópico do carbono como facilidade fenômica para a seleção de algodoeiro em ambientes contrastantes e analisar a sua correlação com os componentes de rendimento. Foram conduzidos experimentos em blocos ao acaso, com quatro repetições, em Santa Helena de Goiás (SHGO) e Montividiu (MONT), GO. A análise da discriminação isotópica do carbono (Δ) foi realizada em 15 linhagens e três cultivares. Em seguida, foram determinadas a cinética de crescimento e a arquitetura do sistema radicular a partir de genótipos selecionados anteriormente. Em ambas as localidades, as análises de Δ mostraram-se adequadas para discriminar os genótipos de algodoeiro. Houve correlação positiva entre Δ e a produtividade de algodão em caroço em SHGO, onde o deficit hídrico foi mais severo. Neste local, as correlações negativas encontradas entre Δ e a percentagem de fibras indicam um efeito integrativo de trocas gasosas sobre Δ e sua associação com componentes de rendimento. Quanto à robustez e à cinética de crescimento do sistema radicular, o desempenho do genótipo GO 05 809 contribui para sustentar os maiores valores de Δ encontrados em MONT, onde as condições edafoclimáticas foram mais adequadas para o algodoeiro. O uso da análise de Δ como facilidade fenômica pode auxiliar a seleção de genótipos de algodoeiro, para a obtenção de plantas com maior eficiência quanto à troca gasosa e ao uso da água.
Fracionamento isotópico do carbono na seleção de genótipo de algodoeiro
Keywords: Gossypium; carbon isotope discrimination; genetic breeding; phenotyping.; Gossypium; discriminação isotópica do carbono; melhoramento genético; fenotipagem.